2005
DOI: 10.1177/0093854804270629
|View full text |Cite
|
Sign up to set email alerts
|

Historical and Personality Correlates to the Violence Patterns of Juveniles Tried as Adults

Abstract: This study examined the utility of several personality indices for explaining variance in the frequency, variety, and situational correlates of past violence exhibited by imprisoned juveniles after controlling for historical risk factors. One hundred prison inmates ages 16 to 21 who were juveniles at the time of their adjudication completed personality measures assessing overcontrolled hostility and psychopathic traits, and they reported on the number and types of past violence and the situational correlates (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
174
1
7

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 200 publications
(198 citation statements)
references
References 53 publications
15
174
1
7
Order By: Relevance
“…For example, Frick and Dickens (2006) reviewed 22 published studies showing either a concurrent (n=10) or predictive (n=12) association between the presence of CU traits and the severity of antisocial and aggressive behavior in children and adolescents. Further, CU traits are not only associated with more severe violence but with violence that seems to be more premeditated and instrumental in nature Kruh, Frick, & Clements, 2005;Pardini, Lochman, & Frick, 2003). The Frick and Dickens (2006) review also reported on 5 additional published studies showing that these traits were related to a poorer response to treatment in antisocial youth.…”
Section: Callous-unemotional Traitsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, Frick and Dickens (2006) reviewed 22 published studies showing either a concurrent (n=10) or predictive (n=12) association between the presence of CU traits and the severity of antisocial and aggressive behavior in children and adolescents. Further, CU traits are not only associated with more severe violence but with violence that seems to be more premeditated and instrumental in nature Kruh, Frick, & Clements, 2005;Pardini, Lochman, & Frick, 2003). The Frick and Dickens (2006) review also reported on 5 additional published studies showing that these traits were related to a poorer response to treatment in antisocial youth.…”
Section: Callous-unemotional Traitsmentioning
confidence: 99%
“…The self-report format has been the most widely used version in adolescent samples and scores from this scale have designated more severe and violent groups of juvenile offenders (Caputo, Frick, & Brodsky, 1999;Kruh et al, 2005), have been associated with an early onset of offending (Silverthorn, Frick, & Reynolds, 2001), and have predicted institutional antisocial behavior and treatment progress in adjudicated adolescents (Spain, Douglas, Poythress, & Epstein, 2004) . Although the correlations between the self-report version of the APSD and the PCL-YV have been modest (typically correlations of .30 to .40; Lee, Vincent, Hart, & Corrado, 2003), scores on the APSD have shown comparable correlations with number of arrests (.33) and number of violent arrests (.25) to the PCL-YV (.36 and .28, all p < .05) in an adolescent offender sample (Salekin, Leistico, Neumann, DiCicco, & Duros, 2004).…”
Section: Callous-unemotional Traitsmentioning
confidence: 99%
“…There has been accumulating evidence for an association of this construct with greater stability and frequency of antisocial behaviors, more serious and violent delinquent behaviors, early onset of criminal activity, early arrests by police and early convictions (e.g., Forth & Book, 2010;Kruh, Frick, & Clements, 2005;Van Baardewijk, Vermeiren, Stegge, & Doreleijers, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…There is growing evidence that at least one component of psychopathy, callous-unemotional (CU) traits (e.g., a lack of guilt and empathy; poverty in emotional expression), may also designate an important and particularly severe subgroup of antisocial youth (see Frick 2006;Frick and Marsee 2006 for reviews). For example, Frick and Dickens (2006) reviewed 24 published studies using 22 independent samples that have shown that the presence of CU traits designates a particularly severe and aggressive group of antisocial youth in both adjudicated (e.g., Kruh et al 2005) and non-adjudicated (e. g., Frick et al 2003) samples, and predicts future aggressive and violent behavior in adjudicated (e.g., Vincent et al 2003) and non-adjudicated (e.g., Frick et al 2005) adolescents.…”
mentioning
confidence: 99%
“…Fourth, the majority of research on the predictive utility of psychopathy in adults and CU traits in children has been conducted with primarily Caucasian samples (see Douglas et al 2006;Frick and Dickens 2006 for reviews of the adult and child literature, respectively). The few studies that have utilized samples with significant minority representation in both adult (Richards et al 2003) and adolescent (Hicks et al 2000;Kruh et al 2005) offending samples have shown comparable associations between CU traits and severity of offending. However, there is also evidence that measures of these traits may show differences at both item and scale level across ethnic groups (Cooke et al 2001;Skeem et al 2004).…”
mentioning
confidence: 99%